Contextualization Of The Hadith Meaning About Work Ethics During The Covid-19 Pandemic - Eka Damayanti; Hamsah F; Ekawati Hamzah; Muhammad Rusydi Rasyid (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
The Covid-19 pandemic limits people’s mobility and causes economic decline. To cope with the problem, the government has issued the pre-employment cards but still insufficient to increase people’s incomes. This study aims to prove the contextualization of the meaning of hadith on work ethics during the pandemic using maudhū’i technique. The research is focusing on one hadith narrated by Ahmad bin Hanbal, since this hadith is the most relevant to the pandemic case. The quality of the hadith is analyzed descriptively based on the hadith book. The study found that the work ethic hadith narrated by Ahmad bin Hanbal is valid because it fulfills the continuity of his sanad and narrators 'adil and al-dlabt. The meaning contained in the hadith which is the focus of the study in this paper emphasizes the nobility of people who use their own hands and abilities to work so that they can provide a spirit for the Muslim ummah to continue working to support their families even during the Covid-19 pandemic.